Proximal bronchiolar adenoma with malignant transformation to invasive mucinous adenocarcinoma with 4 years follow-up: a case report and literature review - Yang, Yuan-Hui; Yin, Ke; Xu, Jia-Qi; Xu, Xiao-Ying; Zhang, Jun-Lei; Liu, Ji-Xuan; Feng, Xin-Zhi; Lin, Xiao-Yan (Frontiers in Oncology, 2025)
BackgroundBronchiolar adenoma (BA) is a rare benign tumor originating in the bronchial mucosal epithelium and occurring primarily in the periphery of the lung. The most prominent histopathological feature of BA is a double-layer bronchial epithelium containing continuous basal cell layers. However, due to the high mutation frequency of the driver gene, there is still debate as to whether BA has the potential for malignant transformation. In frozen sections, basal cells are difficult to identify under the microscope, which makes it difficult to distinguish from mucinous adenocarcinoma, especially when BA malignancies transform into invasive mucinous adenocarcinoma (IMA), which can only be distinguished by histomorphological criteria, greatly increasing the difficulty of diagnosis.Case summaryIn this paper, we present a case study of a 59-year-old man whose chest computed tomography (CT) revealed a progressively enlarging, high-density nodule over a four-year period in the outer basal segment of the right lower lobe. Consequently, he underwent thoracoscopic wedge resection of the right lower lobe. The postoperative pathological diagnosis revealed BA with mucous gland structure formation combined with partial basal cell loss, raising the possibility of malignant transformation into IMA. Regular postoperative follow-up showed no recurrence or metastasis. Hybridization Capture-based next-generation sequencing (NGS) analysis detected driver gene mutations in Kirsten Rat Sarcoma viral oncogene homolog (KRAS) and Cyclin-Dependent Kinases (CDK) 6 in the case, thereby inferring the malignant transformation of BA into IMA.ConclusionIn this case, the detection of driver gene KRAS mutation and loss of continuity in the basal cell layer within the mucous glandular structures of the nodule suggests the malignant transformation of BA into IMA, inferring the malignant potential of BA.